IMPLEMENTASI LEARNING MANAGEMENT SYSTEM SELAMA PANDEMI COVID-19: SEBUAH TINJAUAN LITERATUR - Wayu Meilastri Wulandari; Rahmi Fahmy; Hendra Lukito (Journal Publicuho, 2022)
The main purpose of this study is to review the current literature on the implementation of a learning management system (LMS) from a student perspective during the COVID-19 pandemic. Specifically, we develop a conceptualization and development of a hypothesis related to the implementation of (LMS) by using a unified theory of acceptance and use of technology (UTAUT). Using a qualitative literature review, we establish a new model and six hypotheses regarding the relationship between performance expectancy, effort expectancy, social influence, facilitating conditions, personal innovativeness, LMS adoption, and learning performance. This model can be examined by future research.